PENGARUH PEMANFAATAN SARANA PEMBELAJARAN TERHADAP KOMPETENSI DOSEN UNIHAZ - Nurmintan Silaban (UNIVERSITAS BENGKULU, 2017)
Abstract: The Study aims to reveal the effect of the use of learning facilities on the competence level of leeturers Unihaz. This research uses quantitative approach then analyzed based on statistical analysis with Linear Regression using SPSS 17.0 application. respondents for this research are all Unihaz lecturerrs. Data collection in the research is observation, documentation and questionnaire. The conelision in this research is the learning tool has been utilized in the learning activity in Unihaz Bengkulu competence level is increasing in carrying out learning activities. There is a significant influence between the use of learning facilities to the competence of teaching lecturers Keywords: influence, means of learning, lecturer competence